The Thermodynamic Difference Rule (TDR) for non-aqueous solvates. Part 2. Review of methodology, investigation and prediction of thermodynamic data for ammoniate solvates, MpXq.nNH3, routes to expand the database. (August 2019) - Jenkins, H. Donald Brooke
Highlights: Estimation methods for obtaining new NH3 -ammoniate solvate thermochemical data. Validation methods for existing data. Thermodynamic Difference Rules (TDR). Simple relationships found for thermochemical data. Abstract: This paper investigates methods of estimating new and validation of existing standard thermodynamic data, Δf G o, Δf H o and S o 298 for ammoniate solvates, Mp Xq . nNH3 at 298 K and describes how to identify errors in existing data. A new approach enabling extension of the whole ammoniate database is presented which involves using thermodynamic data for hydrates, Mp Xq . nH2 O and SO2 solvates, MpXq.nSO2 as and if available. This supplements the normal TDR approach which uses the thermodynamic data for parent compounds, Mp Xq. Several TDR equations are introduced and used: Δ f G o ( M p X q . n H 2 O, s ) [ Δ f G o ( M p X q . n H 2 O, s ) / kJ · mo l - 1 = θ Gf H 2 O, s - s . n = −242.4 n (N = 93, R 2 = 0.998 ) [ Δ f H o ( M p X q . n H 2 O, s ) - Δ f H o ( M p X q, s ) ] / kJ · mol - 1 = θ Hf H 2 O, s - s . n = −298.6 n (N = 342, R 2 = 0.999 ) S 298 o ( M p X q . n H 2 O, s - S 298 o ( M p X q, s ) ] / J · K - 1 mol - 1 = θ So H 2 O, s - s . n = 40.9 n (N = 83, R 2 = 0.978 ) [ Δ f H o ( M p X q . n NH 3, s ) - Δ f H o ( M p X q, s ) ] / kJ · mol - 1 = θ Gf NH 3, s - s . n = −21.0 n (N = 4, R 2 = 0.922 ) [ Δ f H o ( M p X q . n NH 3, s ) - Δ f H o ( M p X q, s ) ] / kJ · mol - 1 = θ Gf NH 3, s - s . n = −104.2 n (N = 277, R 2 = 0.930 ) S 298 o M p X q . n NH 3, s - S 298 o M p X q, s ]/J· K - 1 ·mol −1 = θ So ( NH 3, s - s ) . n = 64.1 n (N = 9, R 2 = 0.989 ) Δ f G o ( M p X q . n SO 2, s - Δ f G o ( M p X q, s ) ] / kJ · mol - 1 = θ Gf SO 2, s - s . n = −299.9 n (N = 2, R 2 = 1.00 ) Δ f H o M p X q . n SO 2, s - Δ f H o ( M p X q, s ) /kJ·mol −1 = θ Hf (S O 2, s - s ) . n = - 338.3 n (N = 9, R 2 = 0.999 ) S 298 o M p X q . n SO 2, s - S 298 o ( M p X q, s ) /J· K - 1 ·mol −1 = θ So (S O 2, s - s ) . n = 106.9 n (N = 2, R 2 = 0.999 ) [ Δ f G o ( M p X q . n NH 3, s ) - Δ f G o ( M p X q . n SO 2, s ) ] / kJ ·mol −1 = 278.9 n [ Δ f H o ( M p X q . n NH 3, s ) - Δ f H o ( M p X q . n SO 2, s ) ] / kJ ·mol −1 = 234.1 n S 298 o ( M p X q . n NH 3, s - S 298 o ( M p X q . n SO 2, s ) ] / J · K - 1 ·mol −1 = - 42.8 n [ Δ f G o ( M p X q . n NH 3, s ) - Δ f G o ( M p X q . n H 2 O, s ) ] / kJ ·mol −1 = 221.4 n [ Δ f H o ( M p X q . n NH 3, s ) - Δ f H o ( M p X q . n H 2 O, s ) ] / kJ ·mol −1 = 194.4 n S 298 o ( M p X q . n NH 3, s - S 298 o ( M p X q . n H 2 O, s ) ] / J · K - 1 ·mol −1 = 23.2 n .